KEBIASAAN SOSIAL-BUDAYA DAN TRADISI KEAGAMAAN YANG MEMUDAR DI MASYARAKAT PRAMBANAN PASCA ORDE BARU - M. Alie Humaedi (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2013)
Prambanan is not a huge reflection of Indonesia. However, this boundary territory of Yogyakarta and Central Java, in addition to the birthplace of party founders, is a competition arena between nationalistic parties and religious parties. The PDI supporters, mostly culture-based muslims compete competitively with those of PAN and PKS, mostly theology-based muslims in the context of Muhammadiyah. Such a competition is embodied through socio-cultural and political practices among the local people. PKS often works together with Muhammadiyah or PAN and vice versa, in political campaign as well as political work. Due to this way, PKS successfully put itself in the second position of the General Election in 2009 and so has made a significant influence on the local people’s fading socio-cultural habits. This paper questions the capacity and existence of religious parties in the local political competition, before and after the General Election in 2009, which gives an impact on the people’s life.